Tillage and planting methods effects on yield, water use efficiency and profitability of soybean-wheat system on a loamy sand soil - Ram, Hari; Singh, Yadvinder; Saini, K.S.; Kler, D.S.; Timsina, J. (Cambridge University Press, 2013)
Continuous rice–wheat (RW) cropping with intensive tillage has resulted in land degradation and inefficient use of water in Indo-Gangetic Plains (IGP) of South Asia. Replacement of rice with less water requiring crops such as soybean in RW system and identification of effective strategies for tillage management could result in sustainable cropping system in IGP. A field experiment was conducted for five years on an annual soybean–wheat (SW) rotation in the northwest IGP of India to evaluate effect of tillage, raised bed planting and straw mulch on yield, soil properties, water use efficiency (WUE) and profitability. In soybean, straw mulch reduced soil temperature at seeding depth by about 2.5 °C compared with no mulch. Straw mulch also resulted in slightly reduced water use and slightly higher WUE relative to their respective unmulched treatments. During wheat emergence, raised beds resulted in higher soil temperature by 1.6 °C compared with flat treatments. Bulk density and cumulative infiltration were greater in no-tillage compared with conventional tillage. Soil organic carbon in surface layer increased significantly after five years of experimentation. Soybean and wheat yields were similar under different treatments during all the years of experimentation. Soybean and wheat planted on raised beds recorded about 17% and 23% higher WUE, respectively, than in flat layout. The net returns from SW system were greater in no-tillage and permanent raised beds than with conventional tillage. Both no-tillage and permanent raised bed technologies can be adopted for sustainable crop production in SW rotation in northwest IGP. However, more studies are required representing different soil types and climate conditions for making recommendations for other regions of IGP.